Evaluating the performance of kolej komuniti jasin in implementing the UI greenmetric world university rankings: a comparative analysis of 2022 and 2023 data - Mustafa, Mohamad Sanusi binti; Safee, Norhana binti; Ali, Mohd Azuan bin (Southeast Asian Journal of Technology and Science, 2024)
This study evaluates the performance of Kolej Komuniti Jasin in implementing the UI GreenMetric for sustainability during 2022 and 2023. The UI GreenMetric, encompassing categories such as Setting and Infrastructure (SI), Energy and Climate Change (EC), Waste (WS), Water (WR), Transportation (TR), and Education and Research (ED), serves as a comprehensive framework for assessing sustainability in higher education institutions. Our analysis identifies notable improvements in energy management (EC points: 960 to 1210) and waste management (WS points: 750 to 1350), while highlighting areas needing further attention, such as water resource management (WR points: 210 to 450) and education and research (ED points: 935 to 1010). Key challenges include data collection accuracy and resource constraints. To address these, the study suggests enhancing data management systems and fostering a deeper understanding of sustainability concepts among the academic community through targeted training programs. By aligning data analysis with these objectives, we propose strategies to optimize resource allocation and improve overall sustainability performance. This evaluation provides insights into the progress and ongoing challenges in achieving sustainable development in higher education, emphasizing the need for innovative solutions and stakeholder engagement to advance sustainability initiatives.